Improvement in survival of acute myeloid leukemia and myelodysplastic syndrome patients following allogeneic transplant: a long-term institutional experience - Sigmund, Audrey M.; Jiang, Justin; Zhao, Qiuhong; Elder, Patrick; Benson, Don M.; Vasu, Sumithira; Jaglowski, Samantha; Mims, Alice S.; Choe, Hannah; Larkin, Karilyn; Brammer, Jonathan E.; Wall, Sarah A.; et al. (Frontiers in Hematology, 2023)
Background: Allogeneic stem cell transplant (allo-SCT) plays a key role in the treatment of patients with both acute myeloid leukemia (AML) and myelodysplastic (MDS). Outcomes of allo-SCT have improved with optimization of transplant practices. We sought to evaluate trends in survival in AML and MDS patients undergoing allo-SCT at our institution from 1984 to 2018.A retrospective analysis of 900 consecutive AML and MDS patients undergoing allo-SCT was performed. Patients were divided by year of transplant for analysis. Primary endpoints were progression free survival (PFS) and overall survival (OS). Secondary endpoints included non-relapse mortality (NRM), graft-versus-host disease (GVHD), GVHD-free relapse free survival (GRFS), and transplant complications.We found a significant improvement in survival from 1984 to 2018 with 5-year PFS and OS improving from 17% to 49% and 17% to 53%, respectively (statistically significant difference since 2004; p<0.001). There was a significant difference in rates of grade II-IV aGVHD (p<0.001) and chronic GVHD at day +365 with cumulative incidence of both highest from 2014-2018, however, NRM improved across the years with 5-year NRM decreasing from 45% to 21%. Rates of This is a provisional file, not the final typeset article pulmonary infections, hemorrhagic cystitis, veno-occlusive disease, and fungal infections also decreased across the years (p<0.001).We found a significant improvement in survival of AML and MDS patients undergoing allo-HCT over the past several decades. This likely reflects improvements in transplant practices and general supportive care. Post-transplant relapse remains the leading cause of transplant failure in this group.